Armington Product Variety Growth in Small versus Large Countries - Peter Egger; Martin Gassebner; Andrea Lassmann (Swiss Journal of Economics and Statistics, 2009)
Recent work in international economics provides insights into the measurement of product variety change - i.e., the change at the extensive margin of trade - and its consequences for a country's welfare. In such work, the measurement of product variety change is typically taken as given. There is evidence that product variety change is the main source of gains from trade (see Hummels and Klenow, 2005; and Broda and Weinstein, 2006). However, little is known as to what determines product variety growth, e.g., from an Armington perspective as here, and what we can subsequently learn for the inclination of countries, depending on their characteristics, towards trade liberalization. Results in this paper shed first light on a possible nexus between Armingtontype product variety change (i.e., product diversity by virtue of country of origin) and economic size of countries. Our future research will venture to provide an answer to the question about the key determinants of product variety and as to the heterogeneous consequences of trade liberalization across countries.
Keywords: C43; F14; 330; Product variety; Armington differentiation model